2017
DOI: 10.1134/s1607672917030115
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-induced modification of the fibrinogen polypeptide chains

Abstract: By using the mass-spectrometry method, the oxidative modifications of the fibrinogen Aα, Bβ, and γ polypeptide chains induced by its oxidation have been studied. The αC-region has been proven to be the most vulnerable target for the oxidizer (ozone) as compared with the other structural elements of the Aα chain. The Bβ chain mapping shows that the oxidative sites are localized within all the structural elements of the chain in which the β-nodule exhibits high susceptibility to oxidation. The γ chains are the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Recently, Yurina et al [42] revealed that hypochlorite concentration of 500 μmol/mg fibrinogen, but not 50 μmol/mg fibrinogen, leads to fibrinogen fragmentation. Certain modifications induced in the fibrinogen structure by HOCl partly differed from those induced by ozone [43].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Recently, Yurina et al [42] revealed that hypochlorite concentration of 500 μmol/mg fibrinogen, but not 50 μmol/mg fibrinogen, leads to fibrinogen fragmentation. Certain modifications induced in the fibrinogen structure by HOCl partly differed from those induced by ozone [43].…”
Section: Introductionmentioning
confidence: 83%
“…Effect of oxidative stress on fibrinogen was extensively studied mainly on the mesoscopic scale. To the best of our knowledge, only few studies have been performed on more detailed level using either MS to identify the position and nature of the given PTMs (e.g., [35,42,43]) or MD ( [56,57]) to observe the early stages of fibrinogen structural alternations after the PTM induction. In this study, we combined MS and MD in order to describe the mechanism by which PTMs may influence the behavior of fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…We found 253 positions of 307 PTMs, reported in 30 works [ 5 , 6 , 12 , 15 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ] focusing on fibrinogen modified either in vivo or in vitro (see Figure 2 and Table S1 ). The positions of PTMs are reported according to the mature chains, i.e., sequences without a signal peptide.…”
Section: Resultsmentioning
confidence: 71%
“…No effect of oxidation on fibrinogen properties is described in the cited paper, but it can be found in the paper by Rosenfeld et al [13]. It is questionable whether γP(Ox)70 is present in the samples characterized by the latter work, as it is not reported in a paper by Yurina et al [30] which extends the work of Bychkova et al [29]. Both reports originate from the same group and use the same setup for their experiment.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation